A study of pneumatic conveying with high-density AM-using metal powder in a pipe bend. (1st September 2020) - Sheng, Li-Tsung; Xiao, Yi-Lun; Hsiau, Shu-San; Chen, Chih-Peng; Lin, Po-Shen; Jen, Kuo-Kuang
Highlights: Pneumatic conveying system with high-density metal powder were analyzed. Two-phase flow dynamics were investigated by CFD-DEM simulation method. Secondary flow pattern and rotating Dean vortices of the gas flow were discussed. Rope formation/dispersion of the solid particle phase were examined. Experimental validation was conducted to verify the simulation results of the powder flow. Solving engineering design problems related to pneumatic conveying with pipe bend. Graphical abstract: Abstract: In this study, we numerically investigate a pneumatic-conveying system for high-density metal powder via a gas-solid two-phase theory. This conveying system is modeled as a conveying pipeline in an additive-manufacturing (AM)-recycling system. The gas phase is set to nitrogen, and the solid-particle phase is set to be a nickel-superalloy material used in AM. The two-phase-flow dynamics of the transport of metal powders by the pneumatic-conveying process are investigated by the CFD-DEM simulation method. In particular, we focus on the flow characteristics of the gas and solid-particle phases in the region of the conveying-pipe bend. The dynamics of the gas phase are evaluated via the three-dimensional Reynolds-averaged Navier-Stokes (RANS) equations. The metal powders are treated as a discrete phase and modeled via the Lagrangian-tracking approach and solved using Newton's second law. The secondary-flow pattern and rotating Dean vortices of the gas flow are discussed in terms of the conveying-pipe-bend-curvature effect. The rope-formation/dispersion behaviors of the solid-particle phase in the bends of different curvatures are also examined based on particle-gas-interaction forces. Experimental validation is conducted to verify the simulation results of the powder flow. The trajectories and velocity fields of the metal powders in the bends with different curvatures are measured in the experiments. The rope-formation/dispersion behaviors can also be found in the experiments. It is demonstrated that the numerical simulations and experimental observations are generally in good agreement. This framework will potentially aid in investigating recycling processes for AM applications under large metal-powder loadings.